Historical Development of Research Method - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2003)
The article represents historical development of research method - from some elements in the Antiquity till its dominating importance in the new pedagogy. Author gives the attention to antique education, education of the Middle ages, of the Renaissance, classical pedagogy. The new pedagogy is emphasized especially because the research method was dominating in the education theory and practical work of the school. Author analyses and compares the important education theories of G. Kerschensteiner, J. Dewey, H. Armstrong and others, presents their conceptions of research method. The historical sources of research method show that the principle of historicity always is very important. Author emphasizes the importance of this principle in the development of modern didactics especially.
Keywords: history of education; didactics; new pedagogy; education theories research method